2013
DOI: 10.1038/jid.2013.92
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia Yeasts Produce a Collection of Exceptionally Potent Activators of the Ah (Dioxin) Receptor Detected in Diseased Human Skin

Abstract: Malassezia yeasts are commensal microorganisms which under insufficiently understood conditions can become pathogenic. We have previously shown that specific strains isolated from diseased human skin can preferentially produce agonists of the aryl hydrocarbon receptor (AhR), whose activation has been linked to certain skin diseases. Investigation of skin scale extracts from patients with Malassezia associated diseases demonstrated 10–1000 fold higher AhR activating capacity than control skin extracts. LC/MS/MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
139
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 35 publications
1
139
0
Order By: Relevance
“…It has been shown that Malassezia yeasts are able to secrete various indole derivatives as putative AhR ligands that induced the AhR-responsive genes CYP1A1 and CYP1B1 in HaCaT keratinocytes [27]. Nonetheless, it has not been reported whether the AhR plays a role in human keratinocytes in the interaction between keratinocytes and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Malassezia yeasts are able to secrete various indole derivatives as putative AhR ligands that induced the AhR-responsive genes CYP1A1 and CYP1B1 in HaCaT keratinocytes [27]. Nonetheless, it has not been reported whether the AhR plays a role in human keratinocytes in the interaction between keratinocytes and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hydrogen peroxide in skin of vitiligo patients can lead to formation of FICZ (Schallreuter et al, 2012). Common skin-resident yeasts, Malassezia spp., produce the AhR ligands FICZ, ICZ, pityriacitrin, and malassezin (Wille et al, 2001;Gaitanis et al, 2008;Magiatis et al, 2013). LCs produce AhR-dependently the immunosuppressive enzyme indoleamine 2,3-dioxygenase (Jux et al, 2009;Nguyen et al, 2010), which converts tryptophan to kynurenines.…”
Section: B Aryl Hydrocarbon Receptor In the Skinmentioning
confidence: 99%
“…UV light induces CYP1A1 in human skin (Katiyar et al, 2000) and cultured human keratinocytes (Wei et al, 1999;Fritsche et al, 2007). Furthermore, the proposed endogenous AhR ligand FICZ has been detected in UVB-irradiated immortal human keratinocytes , in skin samples from vitiligo patients (Schallreuter et al, 2012), and in skin from patients with seborrheic dermatitis carrying commensal yeasts belonging to the genus Malassezia, which converts tryptophan to several AhR-activating compounds (Magiatis et al, 2013).…”
Section: Aryl Hydrocarbon Receptor In the Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…Tryptophan metabolism produces a variety of indoles that are potent agonists of the aryl alcohol receptor. These indoles (malassezin, indolo[3,2-b] carbazole, pityriacitrin, and indirubin) were found in extracts of skin from SD and PV patients but not in healthy controls (Magiatis et al 2013). The first three of these materials were produced by M. furfur strains isolated from SD patients when these strains were cultivated in L-tryptophan agar (Gaitanis et al 2008).…”
Section: Pathogenesismentioning
confidence: 98%